Evaluation of temperament of identical environment kept and different genotypes goats - Németh, Szabina; Pajor, Ferenc; Gulyás, László; Póti, Péter; Orbán, Martina; Tóth, Tamás (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
The authors completed temperament research among Alpine (n = 62), Saanen (n = 54) and Hungarian Improved breeds originated from a Győr-Moson-Sopron County’s goat stock-farm. The most important aim of the sample survey was the determination of the relation between the temperament and age of the three examined goat breeds. The temperament estimation was fulfilled by scales-test assistance (the estimation of the animal’s behaviour in a 1–5 point range standing on a pair of scales during 30 seconds). The average age of the examined does (n = 181) was 3.17 ± 1.79 years (Saanen: 3.74 ± 1.94; Alpine: 2.66 ± 1.61; Hungarian Improved: 3.21 ± 1.69 year). The average temperament of the examined breeds was 2.77 ± 0.97. It was found statistically differences among breeds (P < 0.001). The calmest breed was Saanen (2.28 ± 0.90), the next breed was Alpine (2.72 ± 0.86) and the highest score has Hungarian Improved (3.24 ± 0.94) goats. Statistically proved negative relation was found between the age and the temperament scores (r = -0.38; P < 0.001), which means, that as the age goes further so decreases the animal’s temperament.
Keywords: Saanen; Alpine; Hungarian Improved; scale test; age